MANAGEMENT OF PSORIASIS THROUGH AYURVEDA- A CASE STUDY - Singh, *Shipra; Tiwari, Swati; Datta Shukla, Gyanendra; Srivastava, Alok Kumar (International Journal of Ayurveda and Pharma Research, 2018)
Psoriasis is one of the most common dermatologic diseases, affecting up to 1% of the world's population. It is a chronic inflammatory skin disorder clinically characterized by erythematous, sharply demarcated papules and rounded plaques, covered by silvery micaceous scale. It has poorly understood etiology and presence of 50% positive family history. Drugs used now a day are basically immunosuppressive which have severe side effects along with remission of disease as well therefore holistic approach of Ayurveda can be a better approach to such disease. Psoriasis due to its different manifestation in different types can be correlated to different types of Kustha mentioned in Ayurveda. So the case being presented here is a male patient with red demarcated patches with severe itching in armpits, groin and nipple.Material and method: The patient was administered with Virechana with Trivritaavaleha followed by Shamana drugs.Results: After Virechana there was the complete improvement in itching and redness of patches was reduced to some extent but after using Shamana drugs there was moderate reduction in all the symptoms along with mild remission.Conclusion: There is need to develop a management for psoriasis which can give benefit on a long run without any adverse effects so, Ayurvedic system of medicine could be answer to this question.